Analysis of Illocutionary Speech Acts in The Movie 'Agak Laen': A Pragmatic Study - Nurainisah, Ela; Wijaya, Monicka; Wiradita, Nayoga; Bastian, Arif Alexander; Yunianti, Eka Pratiwi (Aisyah Journal of English Language Teaching (AIJELT), 2025)
Abstract – Abstract in English This study examines the various categories of illocutionary acts present in the film Agak Laen. The central research question guiding this investigation is: What types of illocutionary acts are utilized in the movie 'Agak Laen'? The primary objective of this research is to systematically categorize the illocutionary acts observed in the film. The methodological approach employed is descriptive qualitative, involving a structured analytical process comprising identification, classification, detailed examination, and final interpretation. Data collection was conducted through repeated viewings of the film, careful listening to character dialogues, and systematic categorization of speech acts based on established linguistic frameworks. The findings reveal that the illocutionary acts in Agak Laen encompass five key types: commissive, representative, directive, expressive, and declarative. Each type serves a distinct communicative function, contributing to the film’s narrative dynamics and interpersonal exchanges. These acts not only facilitate character interactions but also reflect underlying sociocultural nuances embedded within the dialogues. In conclusion, this analysis underscores the significance of illocutionary acts in shaping discourse within cinematic narratives. By identifying and classifying these speech acts, the study highlights their role in conveying intentionality, advancing plot development, and mirroring broader communicative norms. Keywords: Analysis, Illocutionary Acts, Agak Laen Movie, Pragmatics, Speech Act Abstrak – Abstrak Bahasa Indonesia Penelitian ini mengkaji berbagai kategori tindak ilokusi yang terdapat dalam film Agak Laen. Pertanyaan penelitian yang menjadi fokus kajian ini adalah: Jenis-jenis tindak ilokusi apa sajakah yang digunakan dalam film 'Agak Laen'? Tujuan utama penelitian ini adalah untuk mengklasifikasikan secara sistematis tindak ilokusi yang ditemukan dalam film tersebut. Metode yang digunakan adalah kualitatif deskriptif, dengan tahapan analisis meliputi identifikasi, klasifikasi, pemeriksaan mendalam, dan interpretasi akhir. Pengumpulan data dilakukan melalui penayangan berulang film, penyimakan cermat terhadap dialog antarkarakter, serta pengategorian ujaran berdasarkan kerangka linguistik yang mapan. Temuan penelitian mengungkapkan bahwa tindak ilokusi dalam Agak Laen mencakup lima jenis utama, yaitu komisif, representatif, direktif, ekspresif, dan deklaratif. Setiap jenis memiliki fungsi komunikatif yang khas, berkontribusi pada dinamika naratif dan interaksi antartokoh. Tindak ilokusi ini tidak hanya mendukung komunikasi antarkarakter, tetapi juga merefleksikan nuansa sosiokultural yang melatarbelakangi percakapan mereka. Sebagai simpulan, analisis ini menegaskan peran penting tindak ilokusi dalam membentuk wacana di dalam narasi film. Dengan mengidentifikasi dan mengklasifikasikan tindak ujaran tersebut, penelitian ini menggarisbawahi fungsinya dalam menyampaikan maksud, menggerakkan alur cerita, serta mencerminkan norma komunikasi yang lebih luas. Kata Kunci: Analisis, Tindak Ilokusi, Film Agak Laen, Pragmatik, Tindak Tutur